Diagnosis of Varicella-Zoster Virus Infections in the Clinical Laboratory by LightCycler PCR - Espy, Mark J. (American Society for Microbiology, 2000)
Varicella-zoster virus (VZV) causes vesicular dermal lesions which are clinically evident as varicella (primary infection) or zoster (reactivated) diseases. The LightCycler system (Roche Molecular Biochemicals) is a newly developed commercially available system designed to rapidly perform PCR with real-time detection of PCR products using a fluorescence resonance energy transfer. We compared the detection of VZV from dermal specimens by shell vial cell culture (MRC-5) and by LightCycler PCR. Of 253 specimens, VZV was detected in 23 (9.1%) by shell vial cell cultures and 44 (17.4%) by LightCycler PCR directed to a nucleic acid target sequence in gene 28. Twenty-one of 44 (47.7%) specimens were exclusively positive by LightCycler PCR; the shell vial cell culture assay was never positive when DNA amplification was negative (specificity, 100%). VZV DNA was detected in 39 of 44 (88.6%) specimens positive during cycles 10 through 30 of the LightCycler PCR. These VZV DNA-positive specimens (cycles 10 to 30) and 5 of 11 other PCR positive specimens (cycles 31 to 36) were confirmed by another LightCycler PCR directed to another (gene 29) target of the viral genome. For routine laboratory practice, all specimens yielding amplified DNA to the VZV gene 28 target can be considered positive results. The increased sensitivity (91%) of the LightCycler PCR for detection of VZV, rapid turnaround time for reporting results, virtual elimination of amplicon carryover contamination, and equivalent costs compared to shell vial cell culture for detection of VZV indicate the need for implementation of this technology for routine laboratory diagnosis of this viral infection.